The implementation of lean manufacturing and ergonomics in small medium enterprise – Case study - Ahmad Nasser, Mohd Rose; Mohd Fadzil Faisae, Ab. Rashid; Nik Mohd Zuki, Nik Mohamed; Muhammad Aiman Safwan, Jubri (IOP Publishing Ltd, 2021)
Productivity can be increased by eliminating of all wastes. The objective of lean manufacturing is to eliminate wastes. Commonly, there are seven wastes known as transport, inventory, motion, waiting, over processing, overproduction and defects. However, ergonomics is a process to improve the working posture by designing or arranging a workplace, system and material handling. The aim of this study is to improve the productivity through the integration of basic lean manufacturing and ergonomics in the food company. The walkthrough and distribution of questionnaire have been conducted in this company. Each activity was observed to identify non-value-added activity and work related muscular skeletal disorder (WMSD) that affect the productivity by using questionnaire, motion study and Rapid Upper Limb Assessment (RULA). The questionnaire result has shown that the most of wasted motion is in weighing and measuring activity. In addition, all workers in this process were affected by the musculoskeletal disorder at their neck and shoulder. All movement were simulated through Delmia software. The RULA score shows that the worker had experienced pain at the arm and wrist. The score also suggested that the process should be changed immediately. The changes might reduce the worker's pain and increase the productivity.